Hazarat Ibrahim (AS) - Karam , Ambia (Lahore ,Karachi children's publications)
Inspired by Allah (SWT) to call the people to the truth in his community, Ibrahim (AS) faced many tribulations as a result, including being thrown into a raging fire by his own father. Still, throughout all of these tests, Ibrahim never wavered from his faith and submission to Allah (SWT), the one God.